Computing the reciprocal of units in Galois rings - Elia, Michele; Interlando, J. Carmelo [UNESP]; Palazzo, Reginaldo (Taru Publications, 2000)
In this paper we describe three methods for computing the inverse of units in Galois rings, that is, Galois extensions of integer residue rings of prime power order. © 2000 Taylor & Francis Group, LLC.